Synchrony and diachrony of ancient Greek: language, linguistics and philology ; essays in honor of Emilio Crespo - Giannakēs, Geōrgios K. ca. 20./21. Jh.; Conti, Luz; Villa, Jesús Polo de la; Fornieles, Raquel (Trends in classics, 2021)
Frontmatter -- Preface -- Contents -- List of Figures and Diagrams -- List of Tables -- Emilio Crespo Güemes: The Man and the Scholar -- Publications of Prof. Emilio Crespo -- Part I: Epigraphy and Dialectology -- The Ionic of Lampsacus and the Month of Badromion -- Reflexes of Koineization in Ancient Epirote Feminine Names -- Women’s Names in the Lesbian Dialect -- “Nicomachos Made Me!” Palaeography and Self-promotion in Late Archaic Greek Italy -- Αn Arcadian Man Called Βôθις, or Rather Βόθις? -- Verba Volant. Notes on Some Graffiti from Thasos -- Modern Greek Evidence for Ancient Greek Dialects: The Case of Megarian -- Part II: Lexicon, Onomastics, Morphology, and Morphophonology -- The Noun for ‘Horse’ in Mycenaean and Some Related Terms -- Greek δάρδα, ‘Bee’ -- On Some Naming Constructions in Homeric Greek -- On the “Kriaras” Lexicon of Medieval Vulgar Greek: Issues of Substance (MGL) -- Getting There? Greek δύναμαι, ‘Be Able’ -- The Κένταυρος Controversy Revisited: An Old Etymological Puzzle in a Comparative-Mythological Perspective -- μνημονεύω -- Sappho’s Little Cuddly Fawns: A Reply to an Alternative Proposal (Including a Few Remarks on the Semantics of the Adjectives in -ιος and -ειος) -- Main Phonetic Changes in Ancient Greek Obscuring the PIE Ablaut -- Part III: Syntax and Clause Structure -- Reconstructing (Late) Proto-Indo-European Syntax: Absolute Constructions -- Γίγνομαι as the Lexical Passive of the Support Verb ποιέω in Ancient Greek -- On the Use of the Oblique Optative Dependent on Verba Dicendi in Herodotus -- On Negation, Jespersen’s Cycle, and Negative Concord in Post-Classical Greek -- A Construction Grammar Approach to Ancient Greek Argument Structure Constructions -- Past Tenses of Modal Verbs: ἔδει and (ἐ)χρῆν in Attic Tragedy and Comedy -- Relative Time and Narrative in Herodotus and Thucydides -- Part IV: Pragmatics and Discourse -- The Grammaticalization of μέντοι. Genesis and Scope Increase -- Off- and On-record Complaints in Sophocles: An Initial Approach -- A Note on the Anastrophe of περί with the Genitive in Classical Greek -- Impersonalization as a Mechanism of Impoliteness in Aeschines and Demosthenes: A Study of οὐδείς and μηδείς -- Discourse Markers, Interpretation, and Translation in the Lord’s Prayer -- Evolution of πλήν -- Discourse Markers ἔμπᾱς/ἔμπᾱν/ἔμπᾰ Compared with ἔμπης in the Archaic and Classical Periods -- Part V: In the Linguistics-Philology Interstices -- “Love Teaches”: Echoes of a Fragment from Euripides -- Elis in Homer: Language, Archaeology, Epic Tradition -- The Concept of ‘Emphasis’ in Ancient Greek and Indo-European -- A Quantitative Tetrameter for Proto-Indo- European -- Penis ex Machina as ‘Anticlimax’: ἐξέβαλ’, οἰῶ, τὸ ξίφος (Ar. Lys. 155–156) -- Pythagoras and the Magi -- List of Contributors -- Index